Development of wordwall-based e-learning materials to enhance students' mastery of tajweed rules at an naml qur’an house - Asda Amatullah; Ahmad Nurrohim; Zakiyyah Laili Maghfirah; Balqis Sakhaa Ilaafi; Khonsa Adila; Asmahan Hasna Khoirunnisa; Hafiza Afari Cahya; Muh. Hasbi Khilal Zuhri (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research is based on the results of observations and interviews conducted with several elementary school students who attended the afternoon Al-Quran Education Park (TPA) at An-Naml Qur'an House, Surakarta that during the process of delivering tajweed material the teacher only used the lecture method, which is a classical method that only conveys material by using oral and students listen to it. As a result, this method does not involve students, so it is felt that this method is less effective for tajweed material which is the main support in learning the Koran. Based on these facts, researchers then conducted a study that aims to determine the effectiveness, practicality and validity of interactive multimedia-based